Evaluation of extracellular polymeric substances extracted from waste activated sludge as a renewable corrosion inhibitor - Liew Chien Go; William Holmes; Dilip Depan; Rafael Hernandez (PeerJ, 2019)
Background Waste activated sludge (WAS) has recently gained attention as a feedstock for resource recovery. The aim of this study is to investigate the corrosion inhibition efficiencies of extracellular polymeric substances (EPS) extracted from WAS. Methods The studied corrosion inhibitors were tested with carbon steel in 3.64% NaCl saturated with CO2 at 25 °C, which is the typical oilfield environment. They were first prepared by EPS extraction (heating at 80 °C), followed by centrifugation for solid and liquid separation, then the supernatant was freeze-thawed five times for sterilization of microorganisms in WAS to terminate metabolic activities in the test inhibitors to ensure consistency in corrosion inhibition. The EPS mixture (supernatant) was then deemed as the test corrosion inhibitor. The inhibition performance was determined using potentiodynamic polarization scans. Results Waste activated sludge alone showed unsatisfactory inhibition. However, EPS extracted from WAS showed an optimum inhibition of approximately 80% with 1,000 mg/L of inhibitor. The average total solid (TS) and EPS contents of the WAS were 7,330 mg TS/L WAS and 110 mg EPS/g TS, respectively. Three sets of extracted EPS were scanned with fourier-transform infrared spectroscopy (FTIR) and showed almost overlapping curves, yielding the consistent inhibition performance. Discussion The potentiodynamic polarization results indicated that EPS acts as a mixed-type inhibitor which inhibits corrosion on both anode and cathode sites of metal surfaces. Based on the FTIR results, it was assumed that major chemical groups O–H, N–H, C–N, C=O, and C–H contributed to the inhibition by adsorbing on the metal surface, forming a biofilm that acts as a protective barrier to isolate the metal from its corrosive environment. Results show that WAS EPS corrosion inhibitors have inhibition performance comparable to commercial products, signifying their potential in commercialization. This corrosion inhibitor is renewable, biodegradable, non-toxic, and free from heavy metal, making it a superior green corrosion inhibitor candidate. Additionally, turning biomass into value-added product can be beneficial to the environment and, in this case, deriving new materials from WAS could also transform the economics of wastewater treatment operations.